ANALYSIS OF THE MONITORING OF MUNICIPAL INDEX ALERT (IMA) IN STATE OF CEARA: ADVANCES AND CHALLENGES OF MUNICIPALITIES IN THE PERIOD 2004-2010 - Medeiros, Cleyber Nascimento de; Gomes, Daniel Dantas Moreira; Albuquerque, Emanuel Lindemberg Silva (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2014)
The present study aims at monitoring the Municipal Index Alert (IMA) in the period between the years 2004 to 2010, aiming to contribute to the progress and challenges municipalities face of adversity on preventive guidelines in the context of semi-arid climate in the State of Ceará, based on analysis and reflection report published annually by IPECE. It was found that the cities of Independência, Madalena, Penaforte e Tauá have always been in the class of high vulnerability. These municipalities have as main characteristic having low rainfall, is also vulnerable with respect to agricultural production.